Intensely phosphorescent block copolymer micelles containing gold(i) complexes. Issue 18 (19th April 2018) - Guo, Pingxia; He, Qun; Wang, Chen; Hou, Zaili; Yu, Bingran; Bu, Weifeng
Abstract : Micellization of anionic block copolymers with cationic gold(i ) complexes induces remarkable phosphorescence enhancement in solution. The extent of the luminescence enhancement increases with increasing molecular weight of the anionic block. Abstract : The electrostatic combination of anionic block copolymers with cationic gold(i ) complexes leads to the formation of spherical micelles, where gold(i )-containing ionic cores were formed with anionic blocks and further stabilized by neutral blocks of polystyrene or poly(ethylene oxide). This self-assembled strategy induces remarkable phosphorescence enhancement of the gold(i ) complexes in solution. The emissive intensity increases unexpectedly with increasing molecular weight of the anionic block that is not coordinated onto the gold(i ) complexes. The intensely phosphorescent micelles formed in water can be utilized as a luminescence bioimaging probe in living cells.